2007
DOI: 10.1080/07853890701618305
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in energy metabolism in cardiomyopathies

Abstract: Despite the fact that the heart requires huge amounts of energy to sustain contractile function, it has limited energy reserves and must therefore continually produce large amounts of adenosine triphosphate (ATP) to sustain function. Fatty acids are the primary energy substrate of the adult heart, with more than 60% of the energy normally obtained from the oxidation of fatty acids, the remainder coming from the metabolism of carbohydrates. Alterations in both the rates of ATP production and the type of energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 132 publications
3
55
0
1
Order By: Relevance
“…Although is has been known that glucose utilization is enhanced after stress in the heart for some time (for review, see refs. 22,40,41), the mechanisms regulating this process are poorly understood. It has been assumed that HIF-1α played an important role in this process, at least after ischemic insults (42), but the transcriptional regulators in hypertrophy were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although is has been known that glucose utilization is enhanced after stress in the heart for some time (for review, see refs. 22,40,41), the mechanisms regulating this process are poorly understood. It has been assumed that HIF-1α played an important role in this process, at least after ischemic insults (42), but the transcriptional regulators in hypertrophy were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid-induced and hyperglycemia-induced cardiomyocyte loss, whether by apoptosis or necrosis, contributes to the pathophysiological progression of the diabetic heart (10,14,26,44,49,59). Glp1r activation attenuates palmitate and ceramide-induced apoptosis in HL-1 atrial cardiomyocytes (39).…”
mentioning
confidence: 99%
“…PGC-1␣ expression is induced by cold exposure, exercise, and fasting in tissue-specific patterns. Studies of murine heart have shown that PGC-1␣ is induced at birth and during postnatal stages coincident with a dramatic energy metabolic maturation that involves a robust mitochondrial biogenic response and switch to reliance on fatty acids as the chief fuel (Lehman et al 2000;Lehman and Kelly 2002;Taha and Lopaschuk 2007;Buroker et al 2008). Overexpression studies in mammalian cells in culture or in transgenic mice have shown that both PGC-1␣ and PGC-1␤ are capable of activating the expression of a cascade of genes involved in mitochondrial biogenesis and respiratory function in adipocytes, cardiac myocytes, and myogenic cells Lehman et al 2000;Lin et al 2002a;St-Pierre et al 2003).…”
mentioning
confidence: 99%